Tackling Humidity with Designer Ionic Liquid-Based Gas Sensing Soft Materials - Esteves, Carina (2022)
No. SCENT‐ERC‐2014‐STG‐639123, 2015–2022) UIDP/04378/2020 UIDB/04378/2020 LA/P/0140/2020 SFRH/BD/113112/2015